Dexamethasone in Indonesian Surgery Lowers Post-Op Pain Medication Use: Deksametason dalam Pembedahan di Indonesia Menurunkan Penggunaan Obat Nyeri Pasca Operasi - Mohammed Qasim Taha; Aseel Nabeel Ibrahim; Ahmed Mejbel Hasan (Universitas Muhammadiyah Sidoarjo, 2024)
Dexamethasone is commonly used to prevent postoperative nausea and vomiting, but its analgesic effects remain uncertain. This study aims to investigate the efficacy of intraoperative dexamethasone in reducing postoperative pain after inguinal hernia repair surgery. Methods: A randomized double-blind, placebo-controlled trial was conducted on eighty ASA class I patients aged 15–30 years at Al-Yarmouk Teaching Hospital in Baghdad, Iraq. Patients received varying intravenous doses of dexamethasone or normal saline during surgery. Pain levels were assessed using verbal analogue pain ratings, and the time to first analgesic consumption was recorded. Results: Analysis revealed that the dexamethasone group had significantly lower postoperative discomfort compared to the control group, with higher doses showing greater efficacy. Specifically, a single intravenous dose of dexamethasone administered at the onset of anesthesia significantly reduced the need for postoperative analgesia. Implications: This study highlights the potential of intraoperative dexamethasone as an effective adjunct for postoperative pain management in inguinal hernia repair surgery. Further research is warranted to optimize dosing strategies and confirm these findings in larger and more diverse patient populations. Highlight: Efficacy of Dexamethasone: Demonstrated significant reduction in postoperative pain. Intraoperative Administration: Single dose at anesthesia onset proved effective. Clinical Implications: Potential for dexamethasone as adjunct in pain management strategies. Keywoard: Dexamethasone, Postoperative Pain, Inguinal Hernia Repair, Analgesia, Randomized Controlled Trial